Current relevance in Croatian: a cognitive account - Stanojević, Mateusz-Milan; Geld, Renata (2005)
Some authors (e.g., Katičić 1991:50 ; Barić et al. 1995:406) describe the Croatian perfekt tense as a tense which expresses an action that was completed in the past, but that has a “ vivid connection with the present” (Katičić 1992:176). Such usage is dubbed gotova sadašnjost (hereafter: the completed present1 ; cf. Katičić 1992:176), and it purportedly connects the consequences of an action to a given moment – that is to say an action that was completed in the past has some ramifications for the present. Our aim in this paper is to prove that the completed present is not a relevant grammatical category in the description of the Croatian perfekt tense, because it is not expressed by symbolic means. More specifically, we claim that the l-participle, believed by Croatian grammarians to be the main element responsible for the completed present, does not inherently express current relevance. Instead, the symbolic core of the Croatian perfekt tense is vague as to whether the process it designates is connected to the present time. We speculate that the current relevance analysis of the perfekt is a result of merging its contextual with its symbolic value. Such a merger relies on the aspectual characteristics of the content verb: whereas perfective verbs facilitate current relevance construal, imperfective verbs do not. This calls for a significant reanalysis of the traditional structuralist view of the role of current relevance in Croatian grammar.
Projekt MZOS
Projekt MZOS
ENG